2019
DOI: 10.1002/pbc.27671
|View full text |Cite
|
Sign up to set email alerts
|

Measurable residual disease monitoring using Wilms tumor gene 1 expression in childhood acute myeloid leukemia based on child‐specific reference values

Abstract: Background Measurable/minimal residual disease (MRD) monitoring can predict imminent hematological relapse in acute myeloid leukemia (AML). The majority of childhood AML patients do not harbor fusion genes or mutations applicable as MRD markers and overexpression of Wilms tumor gene 1 (WT1) may constitute a useful monitoring target. However, age‐specific reference values in healthy hematopoiesis and standardization of WT1 assessment are prerequisites for clinical utility. Procedure We investigated WT1 expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
2
3
0
Order By: Relevance
“…The incidence of WT1 gene overexpression in pediatric AML, as reported in previous studies, ranges from 76% to 83% (9, 15-17), which aligns with the current results. However, Juul-Dal et al showed a much lower incidence of WT1 overexpression (45%) (1). Previous pediatric studies showed that WT1 gene overexpression was significantly associated with M4 FAB subtype, this goes in agreement with our results (91.4% of M4 cases had high WT1 levels, p=0.018) (9,18,19).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The incidence of WT1 gene overexpression in pediatric AML, as reported in previous studies, ranges from 76% to 83% (9, 15-17), which aligns with the current results. However, Juul-Dal et al showed a much lower incidence of WT1 overexpression (45%) (1). Previous pediatric studies showed that WT1 gene overexpression was significantly associated with M4 FAB subtype, this goes in agreement with our results (91.4% of M4 cases had high WT1 levels, p=0.018) (9,18,19).…”
Section: Discussionsupporting
confidence: 92%
“…Previous pediatric studies showed that WT1 gene overexpression was significantly associated with M4 FAB subtype, this goes in agreement with our results (91.4% of M4 cases had high WT1 levels, p=0.018) ( 9 , 18 , 19 ). A high incidence of WT1 overexpression in CBF AML was reported, ranging from 87% up to 100% (p<0.001), while a strong inverse correlation with the presence of KMT2A gene rearrangement (p<0.001) suggesting downregulation of WT1 activating pathway in this leukemia subset, as demonstrated in the present study ( 1 , 9 , 20 ).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Overexpression of WT1 has been found to predict poor prognosis and minimal residual disease in AML(Adnan-Awad et al, Becker et al, 2010;Løvvik Juul-Dam et al, 2019). Prkd1 encodes a serine/threonine protein kinase and is part of all top 3 ranked GO terms enriched for persistent events.…”
Section: Discussionmentioning
confidence: 99%